Gastrointestinal nematode control practices on lowland sheep farms in Ireland with reference to selection for anthelmintic resistance - Patten Thomas (Irish Veterinary Journal, 2011)
Abstract Gastrointestinal parasitism is a widely recognised problem in sheep production, particularly for lambs. While anthelmintics have a pivotal role in controlling the effects of parasites, there is a paucity of data on how farmers use anthelmintics. A representative sample of Irish lowland farmers were surveyed regarding their parasite control practices and risk factors that may contribute to the development of anthelmintic resistance. Questionnaires were distributed to 166 lowland Irish sheep producers. The vast majority of respondents treated their sheep with anthelmintics. Lambs were the cohort treated most frequently, the majority of farmers followed a set programme as opposed to treating at sign of disease. A substantial proportion (61%) administered four or more treatments to lambs in a 'normal' year. Departures from best practice in anthelmintic administration that would encourage the development of anthelmintic resistance were observed. In conclusion, in the light of anthelmintic resistance, there is a need for a greater awareness of the principles that underpin the sustainable use of anthelmintics and practices that preserve anthelmintic efficacy should be given a very high priority in the design of helminth control programmes on each farm. To this end, given that veterinary practitioners and agricultural advisors were considered to be the farmer's most popular information resource, the capacity of these professions to communicate information relating to best practice in parasite control should be targeted.